Peningkatan Kapasitas Preceptor dalam Pembelajaran Preceptorship di Rumah Sakit Solo Raya - Setianingsih Setianingsih; Istianna Nurhidayati; Sri Sat Titi; Retno Yuli Hastuti; Saifudin Zukhri; Daryani Daryani (Universitas Muhammadiyah Klaten, 2023)
Preceptorship is a clinical learning process that aims to help students in their new role to acquire initial competencies in a short period of time. Preceptors are often faced with many demands but they are not well prepared to accomplish these demands. Capacity building of preceptors is an effort for clinical supervisors by providing specialized training for the practice of nursing professional education. This activity aims to ensure harmony and readiness in the nursing professional education process. This capacity building is expected to improve the ability of preceptors to provide guidance to nursing students so that students on the practice field can achieve competence in each phase. Capacity building for preceptors was carried out at Politeknik Insan Husada Surakarta on March 16-17, 2023 with 43 participants. This capacity building increases preceptor knowledge with a significance value of 0.000 (α < 0.005). Participants actively participated in the activity and could immediately play an active role in the role play. Role play was carried out by dividing participants into 5 groups. The materials presented in this activity include effective communication in pre and post conferences, Bed Side Teaching, Journal and Presus Analysis, Mini Cex and DOPS. The ability to facilitate students in learning in the clinic is seen when preceptors do role play. Preceptors can perform their roles very well.